QARAQALPAQ XALÍQ QOSÍQLARÍNÍŃ RAWAJLANÍWÍNDA KOMPOZITOR Ǵ.AMANIYAZOVTÍŃ TUTQAN ORNÍ - Eshbaeva, G. (SCIENCE and SOCIETY, 2024)
This article examines the role of the composer G.Amaniyozov in the development of Karakalpak folk songs and his close connection with the life of the people.